Medieval rural settlement (Oxford)
xii, 369 s.
Keywords: "Medieval Rural Settlement: Britain and Ireland, AD 800-1600 is a major assessment and review of the origins, forms and evolutions of medieval rural settlement in Britain and Ireland across the period c. AD 800-1600. It offers a comprehensive analysis of early to late medieval settlement, land use, economics and population, bringing together evidence drawn from archaeological excavations and surveys, historical geographical analysis and documentary and place-name study. It is intended to be the flagship publication of the Medieval Settlement Research Group (MSRG) which has a long and distinguished history of exploring, debating and promoting research and offers systematic appraisal of 60 years' work across the whole field of medieval settlement, designed to inspire the next generation of researchers. Part I comprises a set of papers exploring the history of medieval rural settlement research in Britain and Ireland, the evolving methodologies, the roots of the medieval landscape and the place of power in these settlements and landscapes. Part II presents an extensive series of regional and national reviews detailing contexts, histories of study, forms, evolutions and future research needs. These extensive contributions also include "feature boxes" on key themes, sites to visit and main excavations in the study areas discussed. A final section provides guidance on how to research and study medieval rural sites - from laptop to test-pit. Extensively illustrated in colour and black and white, and written by expert contributors, the volume includes a comprehensive, integrated bibliography and an index. Medieval Rural Settlement: Britain and Ireland, AD 800-1600 will be essential reading for everyone researching and interested in medieval settlements and the medieval rural landscape." --